Femtosecond excited state dynamics of stilbene–viologen complexes with a weakly pronounced charge transfer. Issue 9 (23rd July 2020) - Rusalov, Mikhail V.; Volchkov, Valery V.; Ivanov, Vladimir L.; Melnikov, Mikhail Ya.; Gostev, Fedor E.; Shelaev, Ivan V.; Nadtochenko, Victor A.; Vedernikov, Artem I.; Gromov, Sergey P.; Alfimov, Michael V.
Abstract : Charge transfer complexes between bis(18-crown-6)stilbene and viologen analogues. A femtosecond study of photoinduced electron transfer. Abstract : The femtosecond dynamics of photoinduced electron transfers in supramolecular donor–acceptor complexes between ( E )-bis(18-crown-6)stilbene (D ) and tetraperchlorates of 2, 7-di(2-ammonioethyl)(2, 7-diazapyrenium) (A1 ), 3, 3′-( E )-ethene-1, 2-diylbis[1-(3-ammoniopropyl)pyridinium] (A2 ) and 4, 4′-ethane-1, 2-diylbis[1-(3-ammoniopropyl)pyridinium] (A3 ) was studied. The acceptors A2 and A3 are weak electron acceptors whose first reduction potentials are equal to −1.0 and −1.2 V (Ag), respectively, while A1 is a strong acceptor with a reduction potential of −0.42 V. It was shown that the back electron transfer time in CT-states of the complexes D·A2 and D·A3 is 30–40 ps, which is approximately 50 times greater than the analogous time for the charge transfer complexes studied earlier. The complex D·A1 is characterized by ultrafast back electron transfer (770 fs). The relaxation pathway of excited states of D·A1 depends on the wavelength of the excitation light. When excited at 356 nm, the accumulation of a transient locally excited (LE) state with a 250 fs lifetime was observed. But when excited at 425 nm, the formation of the LE-state was not observed.